Preliminary symbiotic performance of indigenous soybean (Glycine max)-nodulating rhizobia from agricultural soils of Tanzania - Nakei, Monica D.; Venkataramana, Pavithravani B.; Ndakidemi, Patrick A. (Frontiers in Sustainable Food Systems, 2023)
Worldwide increase in human population continues to threaten the sustainability of agricultural systems. Sub-Saharan Africa (SSA) is among the regions with a fast-growing population but decreasing crop productivity. The decrease is primarily attributed to continuous growing and harvesting of crops without replenishment of soils leading to inadequate levels of nutrients in soil to support optimum growth and development of crops. In SSA, smallholder farmers are the major producers of food crops. However, smallholder farmers rarely use fertilizers. This is due to unaffordability of the cost of fertilizers, which are enough to suffice the crop requirement. There is therefore, a need for alternative affordable, effective and environmentally friendly fertilization methods for sustainable intensification and improvement of smallholder farming systems. This study was conducted to evaluate the symbiotic performance of indigenous soybean nodulating rhizobia in the selected agricultural soils of Tanzania. The 217 rhizobia isolates were obtained from three agro-ecological zones i.e., eastern, northern, and southern highlands. The isolates were screened for N2-fixing abilities under in vitro (nitrogen free medium) and screen house conditions. Results showed varying capabilities of isolates in fixing nitrogen both under in vitro and screen house conditions. Under in vitro experiment, 22% of soybean rhizobia isolates were capable of fixing on N free medium. In the screen house pot experiment results showed that the soybean rhizobia isolates significantly (P < 0.001) increased nodule numbers and dry weight and enhanced plant growth parameters including shoot length, and shoot and total plant dry weights. Furthermore, rhizobia isolates significantly (P = 0.038) increased root dry weight. Results also indicated that 51.39% of the tested bacterial isolates were highly effective suggesting promising potential as alternative bio-fertilizers for soybean production in agricultural soils of Tanzania.